2015
DOI: 10.2135/cropsci2014.07.0497
|View full text |Cite
|
Sign up to set email alerts
|

Hierarchical Bayesian Modeling for Flexible Experiments in Decentralized Participatory Plant Breeding

Abstract: Decentralized participatory plant breeding (PPB) is a method for creating new varieties adapted to agroecology based systems. Selection is decentralized in the target environments and relies on collaboration between farmers, Non Governmental Organizations (NGOs), and researchers. In the wheat PPB project studied, the decentralization was extensive as each farmer participating in the project performed the selection experiment on his farm. This led to unbalanced designs with few residual degrees of freedom avail… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(26 citation statements)
references
References 48 publications
0
23
0
3
Order By: Relevance
“…This is the case of the bread wheat PPB program that was studied here. In previous studies, we showed that on-farm evaluation and selection of populations can be organized through specific experimental devices that have been adapted to fit to a large number of small size trials with limited replication of entries within and among trials [6,7]. This is very flexible and convenient for the farmers, as only a small number of common controls are replicated within and among farms, and the rest of entries are populations chosen by each farmer on their farm.…”
Section: The Whole Range Of Outcomes Of Ppb Programsmentioning
confidence: 99%
See 2 more Smart Citations
“…This is the case of the bread wheat PPB program that was studied here. In previous studies, we showed that on-farm evaluation and selection of populations can be organized through specific experimental devices that have been adapted to fit to a large number of small size trials with limited replication of entries within and among trials [6,7]. This is very flexible and convenient for the farmers, as only a small number of common controls are replicated within and among farms, and the rest of entries are populations chosen by each farmer on their farm.…”
Section: The Whole Range Of Outcomes Of Ppb Programsmentioning
confidence: 99%
“…Indeed, on-farm evaluation and selection of heterogeneous populations lead to methodological challenges in the set-up of adapted experimental designs and in the analyses of data, because each on-farm trial is often of small size, with a limited number of plots, and a low level of replication [6,7]. Several PPB programs have therefore developed or adapted original designs and methods that allow farmers to compare several populations on their farms, to select the most adapted and to pursue the process over several years [6][7][8][9]. To facilitate the implementation of experimental designs suitable for on farm evaluation and selection and the analysis of data generated by PPB programs, an R package, PPBstats, is under development to implement many of these statistical analyses for agronomic and molecular data, organoleptic tests, and seed circulation networks [10].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cependant les scientifiques avaient besoin de faire des analyses statistiques pour comparer les populations au sein d'une ferme et entre fermes. Après un ou deux ans de tâtonnements et discussions, un compromis a été trouvé qui repose sur l'optimisation de quelques témoins répétés et le développement de nouvelles méthodes d'analyse statistique (approche bayésienne, Rivière et al, 2015a). De nombreux exemples pourraient être donnés de ces efforts de co-construction.…”
Section: S56unclassified
“…Soc. 25, S55-S59 (2017) S57 populations, construction de mélanges...) (Rivière et al, 2013(Rivière et al, , 2015a.…”
Section: S56unclassified